2007
DOI: 10.2337/db06-0753
|View full text |Cite
|
Sign up to set email alerts
|

Glucotoxicity in the INS-1 Rat Insulinoma Cell Line Is Mediated by the Orphan Nuclear Receptor Small Heterodimer Partner

Abstract: Prolonged elevations of glucose concentration have deleterious effects on ␤-cell function. One of the hallmarks of such glucotoxicity is a reduction in insulin gene expression, resulting from decreased insulin promoter activity. Small heterodimer partner (SHP; NR0B2) is an atypical orphan nuclear receptor that inhibits nuclear receptor signaling in diverse metabolic pathways. In this study, we found that sustained culture of INS-1 cells at high glucose concentrations leads to an increase in SHP mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 39 publications
(37 reference statements)
2
45
0
Order By: Relevance
“…Several mechanisms have been implicated in these effects of glucotoxicity, including ceramide formation [4], oxidative stress [5] and inflammation [6]. Alterations in the gene expression of pancreas-specific transcription factors, including pancreatic duodenal homeobox 1 (Pdx-1), beta cell E-box transcription factor (Beta2)/neuronal differentiation 1 (NeuroD; also known as NEUROD1) and v-maf musculoaponeurotic fibrosarcoma oncogene family, protein A (avian) (Mafa), contribute to the induction of beta cell dysfunction [7][8][9][10][11]. Our group has reported that the suppression of Beta2/NeuroD transcription by overexpression of the gene encoding peroxisome proliferator-activated receptor γ-coactivator-1α (Pgc-1α; also known as Ppargc1a) is an important initial step in beta cell glucotoxicity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been implicated in these effects of glucotoxicity, including ceramide formation [4], oxidative stress [5] and inflammation [6]. Alterations in the gene expression of pancreas-specific transcription factors, including pancreatic duodenal homeobox 1 (Pdx-1), beta cell E-box transcription factor (Beta2)/neuronal differentiation 1 (NeuroD; also known as NEUROD1) and v-maf musculoaponeurotic fibrosarcoma oncogene family, protein A (avian) (Mafa), contribute to the induction of beta cell dysfunction [7][8][9][10][11]. Our group has reported that the suppression of Beta2/NeuroD transcription by overexpression of the gene encoding peroxisome proliferator-activated receptor γ-coactivator-1α (Pgc-1α; also known as Ppargc1a) is an important initial step in beta cell glucotoxicity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SHP has been demonstrated to perform a significant function in the development of β cell dysfunction induced by glucotoxicity, when a sustained culture of INS-1 cells at high glucose concentrations resulted in an increase in the expression of SHP mRNA, followed by a reduction in insulin gene expression. Additionally, the proposed mechanisms for the downregulation of insulin gene expression by SHP suggested (i) the downregulation of PDX-1 and MafA gene expression and (ii) the inhibition of p300-mediated PDX-1 and BETA2-dependent transcriptional activity at the insulin promoter [100].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…When glucotoxicity occurs, β-cell damage leads to defects in insulin production such that chronic glucose exposureinduced β-cell exhaustion becomes irreversible. Some of the explanations for glucoseinduced β-cell damage include depressed rates of insulin synthesis [450], increased small heterodimer partner (SHP) nuclear receptor mRNA [451], downregulation of glucokinase mRNA [425], reduced PDX-1 mRNA, protein and insulin promoter binding activity [312,450,452], compromised mitochondrial function and induction of apoptosis. Upregulation of the SHP receptor is thought to act as a competitive inhibitor to prevent p300-mediated PDX-1 and BETA2 complex formation [451].…”
Section: Glutotoxicity -Glycation and Reactive Oxygen Species (Ros) Pmentioning
confidence: 99%
“…Some of the explanations for glucoseinduced β-cell damage include depressed rates of insulin synthesis [450], increased small heterodimer partner (SHP) nuclear receptor mRNA [451], downregulation of glucokinase mRNA [425], reduced PDX-1 mRNA, protein and insulin promoter binding activity [312,450,452], compromised mitochondrial function and induction of apoptosis. Upregulation of the SHP receptor is thought to act as a competitive inhibitor to prevent p300-mediated PDX-1 and BETA2 complex formation [451]. Repeated exposure to elevated glucose also reduces activity of RIPE3b1 [453,454], while enhancing activity of insulin transcriptional repressor basic leucine zipper CCAAT/enhancer-binding protein β (C/EBPβ) [455,456].…”
Section: Glutotoxicity -Glycation and Reactive Oxygen Species (Ros) Pmentioning
confidence: 99%